Contraception with the lactation amenorrhea: knowledge and practice of nurses - Giselle Lima de Freitas; Escolástica Rejane Ferreira Moura (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The assistance in family planning in Brazil is being developed primarily by the Family Health Program (FHP), a strategy of public policy aimed to change the biomedical model of health care, turning up primarily to health promotion. In this context, is the nurse as the main responsible for assistance in family planning. The country approves various methods of contraception, such:hormonal oral and injectable, combination or exclusively of progestogen, male and female condom, diaphragm, spermicide, intra-uterine device (IUD), tubal ligation, vasectomy and emergency pill, and the natural method of contraception or the method of lactation with amenorrhea (LAM) and the behavioral methods (table or Ogino-Knaus, cervical mucus or method of Billings, basal temperature or sintotérmico and coitus interrupted). However, an uneven distribution of methods, mainly to the interior, and a small variety, brings high rates of abortion and unwanted pregnancies. Therefore it is necessary to promote natural methods, highlighting the method of LAM, by his double benefit to the child and maternal health.